The interactive edutainment platform for primary level mathematics - Su, Li (2020)
Interactive edutainment platform help student to gain learning material quickly and heighten in their studies. Most of the students elect to occupy most of their time on mobile or any other device in this day and age. Learner will be more savour to gain additional knowledge when saw some innovative animation or graphic rather than just construe using text. Through the use of online edutainment platform, user can increase to acquire new knowledge and skill. Besides, students may perceive more unrestrained to learn individually during their leisure hours. Different learning surrounding help to boost learning mood and flush increase comprehension during the course of learning. Therefore, the main target is to become more approachable and undemanding to incorporate into the educational process with the usage and combination of edutainment. Furthermore, help to promote and increase the interest topics that students might otherwise disregard is one of the accomplishments of edutainment that comprise in variable learning content and resources. This project is target on the mathematics subject and user between age of seven to nine years old students. It divides into three different standard which are standard 1, standard 2 and standard 3. Each of the standard consists of different learning material such as lecture note, tutorial question, video quiz and games. Besides, basic formulas and calculator link are provided in the system for student as a reference. Formula can help student grasp simple calculations like transform between different measurement units. Game is including in the system for students so that they do their revision while play game. Various multimedia elements are included in the system such as animation, graphic, interactive design and features, audio and text. They may feel more interest using any of the online platform rather than a traditional way such as textbook.